CANINE LEPTOSPIROSIS IDENTIFICATION IN SMALL ANIMAL PRACTICE - Erni Sulistiawati; Zulfitra Utami Putri; Cucu K Sajuthi; Dondin Sajuthi; Nurul Oktaviani (Jurnal Kedokteran Hewan, 2022)
Leptospirosis is an infectious disease caused by bacteria from the genus Leptospira with various serovars and often presents with a wide range of clinical signs from mild to severe conditions, particularly it presents with a mild fever to asymptomatic infection-causing animal death. The purpose of this study was to identify the characteristics of canine leptospirosis through laboratory examinations supported by medical record data in a small animal practice at the drh Cucu K. Sajuthi Joint Veterinary Practice, in Jakarta. The study was conducted on serum samples of sixteen dogs from drh Cucu K. Sajuthi Joint Veterinary Practice patients, which presented varied clinical signs of leptospirosis, and which had been accompanied by hematological examination, blood biochemistry, and Microscopic Agglutination Test (MAT) against various serovars such as Bataviae, Icterohaemorrhagiae, and Javanica. The collected data was analyzed descriptively. The results showed that canine leptospirosis was more commonly derived from Bataviae serovar and was accompanied by clinical signs such as vomiting, jaundice, anorexia, abdominal pain, lethargy, pale mucosal membrane, diarrhea, dehydration, dyspnea, and polyuria/polydipsia. A predisposition of gender and age was commonly found in male dogs less than 5 years old. Abnormalities found from hematological examination were leukocytosis, granulocytosis (neutrophilia), anemia, thrombocytopenia, and lymphopenia, while blood chemistry showed azotemia, an increase in liver enzymes (AST, ALT, ALP), hyperbilirubinemia, hyponatremia, hyperphosphatemia, and hypoalbuminemia.